Achieving wideband electromagnetic wave absorbing performance for PMMA-based composites foam by designing the alternating directional (AD) microporous structure - Danfeng Zhou; Zirui Yu; Huan Yuan; Guoqiang Luo; Ruofei Hu; Xueliang Jiang; Qiang Shen (Materials Today Advances, 2023)
Good impedance matching and attenuation ability of electromagnetic wave absorbing (EMA) materials are required to broaden the effective absorbing bandwidth (EAB) and reduce minimum reflection loss (RLmin), achieving high EMA performance. Here we report a polymethylmethacrylate (PMMA)-based composites foam with alternating and directional (AD) microporous structure that possessing broadened EAB value of 3.53 GHz (8.49–12.02 GHz) and lowered RLmin value of −19.35 dB, was manufactured via the one-step physical constraint foaming technology. Structural studies reveal that the AD microporous structure can induce the carbon nanotubes (CNTs) oriented distribution to improve effective concentration of CNTs, achieving excellent impedance matching. Meanwhile, a large number of parallel-plate capacitors at the multilayer layer interfaces were generated to promote interfacial polarization, including enhancement of multiple reflection and scattering of electromagnetic wave at the layer interfaces. Thereby, the composites foams exhibited high attenuation ability. This study lays the foundation for rational design and synthesis of EMA materials for wideband EMA performance.